2020
DOI: 10.3390/brainsci10121005
|View full text |Cite
|
Sign up to set email alerts
|

Navigated TMS in the ICU: Introducing Motor Mapping to the Critical Care Setting

Abstract: Navigated transcranial magnetic stimulation (nTMS) is a modality for noninvasive cortical mapping. Specifically, nTMS motor mapping is an objective measure of motor function, offering quantitative diagnostic information regardless of subject cooperation or consciousness. Thus far, it has mostly been restricted to the outpatient setting. This study evaluates the feasibility of nTMS motor mapping in the intensive care unit (ICU) setting and solves the challenges encountered in this special environment. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The dorsal premotor region (dPM), subthalamic nucleus (STN), dorsal anterior cingulate cortex (dACC), primary somatosensory cortex (S1), and supplementary and pre-supplementary motor areas complex (SMA proper and pre-SMA) are also frequently used as targets [ 37 ]. According to the navigation of functional magnetic resonance imaging (fMRI) results, the precise stimulation of brain regions with abnormal functional connectivity in stroke patients by rTMS can be achieved, and more targets that match individual anatomy or functional physiology can be presented [ 38 , 39 ].…”
Section: Overview Of Neuromodulation and Nibsmentioning
confidence: 99%
“…The dorsal premotor region (dPM), subthalamic nucleus (STN), dorsal anterior cingulate cortex (dACC), primary somatosensory cortex (S1), and supplementary and pre-supplementary motor areas complex (SMA proper and pre-SMA) are also frequently used as targets [ 37 ]. According to the navigation of functional magnetic resonance imaging (fMRI) results, the precise stimulation of brain regions with abnormal functional connectivity in stroke patients by rTMS can be achieved, and more targets that match individual anatomy or functional physiology can be presented [ 38 , 39 ].…”
Section: Overview Of Neuromodulation and Nibsmentioning
confidence: 99%
“…Furthermore, integrating nTMS motor mapping in clinical workflows has provided initial evidence for the usefulness of the method for planning of a stereotactic tumor biopsy, performing endoscopic cystoventriculostomy, or facilitating a transparietal approach to the trigone of the lateral ventricle in patients with brain neoplasms [ 88 , 89 , 90 ]. In a special environment such as the intensive care unit with critically ill patients, an approach for safe and reliable use of nTMS motor mapping has been described recently, yet preliminarily in patients suffering from other diseases than brain tumors (e.g., central cord syndrome after trauma, ischemic or hemorrhagic stroke) [ 91 ]. In particular, the use of computed tomography (CT) instead of MRI data may help to establish nTMS motor mapping also in special environments with patients who may only be eligible to undergo CT due to specific infrastructural constraints (e.g., non-availability of timely imaging by MRI) or medical conditions (e.g., specific implanted devices as contraindications for MRI) [ 91 , 92 ].…”
Section: Clinical Application Of Ntms For Mapping Motor Functionmentioning
confidence: 99%
“…In a special environment such as the intensive care unit with critically ill patients, an approach for safe and reliable use of nTMS motor mapping has been described recently, yet preliminarily in patients suffering from other diseases than brain tumors (e.g., central cord syndrome after trauma, ischemic or hemorrhagic stroke) [ 91 ]. In particular, the use of computed tomography (CT) instead of MRI data may help to establish nTMS motor mapping also in special environments with patients who may only be eligible to undergo CT due to specific infrastructural constraints (e.g., non-availability of timely imaging by MRI) or medical conditions (e.g., specific implanted devices as contraindications for MRI) [ 91 , 92 ]. While this underlines the broad applicability of nTMS motor mapping, which requires little patient interaction while creating valuable data on the motor system in a non-invasive way, high accuracy has to be ensured and other imaging sources than MRI have to be regarded as second-line alternatives in selected cases.…”
Section: Clinical Application Of Ntms For Mapping Motor Functionmentioning
confidence: 99%
“…This Special Issue entitled "Modern Developments in Transcranial Magnetic Stimulation (TMS)-Applications and Perspectives in Clinical Neuroscience" in Brain Sciences received studies covering various applications of TMS, with focuses on neuronavigated TMS (nTMS) for mapping of cortical functions [10][11][12][13][14], treatment and modulatory effects [15][16][17][18][19], and basic neuromechanisms [20][21][22], all clinically relevant and supporting the aims set for the Special Issue.…”
mentioning
confidence: 93%
“…Applying motor mapping in critically ill patients, Schramm et al demonstrated the use of nTMS as a safe and reliable method for motor mapping in the intensive care unit (ICU) setting, and outlined its possible benefits [12]. The authors demonstrated that in the ICU environment, where imaging with computed tomography (CT) is more applicable than magnetic resonance imaging (MRI) that is conventionally used with nTMS, the postprocessed CT images provided a feasible alternative to MRI for neuronavigation [12]. The ICU environment is notoriously challenging, given that electromyography (EMG) for motor mapping with nTMS is highly sensitive to noise coupled to weak signals.…”
mentioning
confidence: 99%